Asia-Pacific Working Group consensus on non-variceal upper gastrointestinal bleeding. Issue 9 (6th April 2011) - Sung, Joseph J Y; Chan, Francis K L; Chen, Minhu; Ching, Jessica Y L; Ho, K Y; Kachintorn, Udom; Kim, Nayoung; Lau, James Y W; Menon, Jayaram; Rani, Abdul Aziz; Reddy, Nageshwar; Sollano, Jose; et al.
Abstract : Upper gastrointestinal bleeding (UGIB), especially peptic ulcer bleeding, remains one of the most important cause of hospitalisation and mortality world wide. In Asia, with a high prevalence of Helicobacter pylori infection, a potential difference in drug metabolism, and a difference in clinical management of UGIB due to variable socioeconomic environments, it is considered necessary to re-examine the International Consensus of Non-variceal Upper Gastrointestinal Bleeding with emphasis on data generated from the region. The working group, which comprised experts from 12 countries from Asia, recommended the use of the Blatchford score for selection of patients who require endoscopic intervention and which would allow early discharge of patients at low risk. Patients' comorbid conditions should be included in risk assessment. A pre-endoscopy proton pump inhibitor (PPI) is recommended as a stop-gap treatment when endoscopy within 24 h is not available. An adherent clot on a peptic ulcer should be treated with endoscopy combined with a PPI if the clot cannot be removed. Routine repeated endoscopy is not recommended. High-dose intravenous and oral PPIs are recommended but low-dose intravenous PPIs should be avoided. COX-2 selective non-steroidal anti-inflammatory drugs combined with a PPI are recommended for patients with very high risk of UGIB. Aspirin should be resumed soon after stabilisation and clopidogrel alone is no safer than aspirin plus a PPI. When dual antiplatelet agents are used, prophylactic use of a PPI reduces the risk of adverse gastrointestinal events.